Pengaruh Penggunaan Bubuk Batu Kapur untuk Ekstrinsik Gigi (Noda) Pada Perokok - Suyatmi, Dwi; Taadi, Taadi (Poltekkes Kemenkes Yogyakarta, 2018)
The use of tobacco products, tea, coffee, certain mouthwashes and pigments in the food causes the formation of stain. The research aimed to determine the effect of limestone powder to the cleaning of extrinsic tooth staining (stain). This study used a quasi-experimental design with the design of pre-test - Post-test Design (Campbell and Stanley, 1966, cit. Arikunto, 2006), the research done by using the first observation (pre-test) before the intervention. Furthermore, the post-test after the intervention to determine changes. Variables that influence of limestone powder. The variable affected is extrinsic tooth discoloration (stain). The results showed that smokers after intervention stain brush his teeth with limestone powder showed that the t value of 5.77 with a probability of 0.001. This probability is below 0.05 (significant p <0.05), the null hypothesis is rejected, which means there are differences between the mean scores before the intervention brushing teeth stain with limestone powder on one observation after intervention by brushing your teeth with limestone powder on observation 2 and third, the intervention After brushing teeth with limestone powder stain mean score decreased from 8.50 becomes 7.23 and 6.53. Conclusion limestone Powder effectively lower extrinsic tooth staining (stain) when done diligently and carefully.